1986
DOI: 10.1111/j.1471-4159.1986.tb00682.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Involvement of Phospholipases A2 and C in the α‐Adrenergic and γ‐Aminobutyric Acid Receptor Modulation of Cyclic AMP Accumulation in Rat Brain Slices

Abstract: Experiments were undertaken to define the role of two calcium‐associated enzyme systems in modulating transmitter‐stimulated production of cylic nucleotides in rat brain. Cyclic AMP (cAMP) accumulation was examined in cerebral cortical slices using a prelabeling technique. The enhancement of isoproterenol‐stimulated cAMP production by α‐adrenergic and γ‐aminobutyric acid‐B (GABAB) agonists was reduced by exposing the tissue to EGTA, a chelator of divalent cations, or quinacrine, a nonselective inhibitor of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…By contrast, baclofen, which is a GABAb receptor agonist, mimicked the effects of ALA on I Na activation and inactivation, suggesting the possible involvement of GABAb receptors in the actions of ALA. GABAb receptors have been shown to be a type of G‐protein‐coupled receptor, the activation of which would lead to multiple intracellular effects, including regulation of phospholipase C (PLC) and A 2 (PLA 2 ), which could be followed by a signaling cascade that liberated arachidonic acid, changed post‐synaptic calcium level, etc. (Duman et al ., 1986; Muzzio et al ., 2001). It was also demonstrated that activation of GABAb receptors could enhance adenylyl cyclase activities by a mechanism involving betagamma subunits of Gi/Go (Olianas & Onali, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, baclofen, which is a GABAb receptor agonist, mimicked the effects of ALA on I Na activation and inactivation, suggesting the possible involvement of GABAb receptors in the actions of ALA. GABAb receptors have been shown to be a type of G‐protein‐coupled receptor, the activation of which would lead to multiple intracellular effects, including regulation of phospholipase C (PLC) and A 2 (PLA 2 ), which could be followed by a signaling cascade that liberated arachidonic acid, changed post‐synaptic calcium level, etc. (Duman et al ., 1986; Muzzio et al ., 2001). It was also demonstrated that activation of GABAb receptors could enhance adenylyl cyclase activities by a mechanism involving betagamma subunits of Gi/Go (Olianas & Onali, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in brain slices have suggested that facilitation of cyclic AMP formation occurs indirectly, as a consequence of phospholipase A2 stimulation by GABA B receptors and may be mediated by arachidonate or some other fatty acid (Duman, Karbon et al 1986).…”
Section: Coupling To Adenylyl Cyclasementioning
confidence: 99%
“…A number of studies have reported many factors which can lead to modulation of GABA B receptors such as cross-talks with other receptors or pathways and interaction with GABA B R associate proteins (Karbon, Duman et al 1984;Karbon and Enna 1985;Duman, Karbon et al 1986;Schaad, Schorderet et al 1989;Olianas and Onali 1999;Simonds 1999;Bowery and Enna 2000;Kubota, Katsurabayashi et al 2003;Balasubramanian, Teissere et al 2004) Cross-talks between PKA and PKC pathways which affect GABA release have also been reported. It has been suggested that the PKC cascade has no direct effects on GABA release, but it is involved in GABA release via cross-talk with the cAMP/PKA (Kubota, Katsurabayashi et al 2003).…”
Section: Modulation Of Gaba B Receptor Functionmentioning
confidence: 99%